Cdc42 regulates bone modeling and remodeling in mice by modulating RANKL/M-CSF signaling and osteoclast polarization - Ito, Yuji (American Society for Clinical Investigation, 2010)
The modeling and remodeling of bone requires activation and polarization of osteoclasts, achieved by reorganization of the cytoskeleton. Members of the Rho subfamily of small GTPases, including Cdc42, are known regulators of cytoskeletal components, but the role of these proteins in bone physiology and pathophysiology remains unclear. Here, we examined loss-of-function mice in which Cdc42 was selectively ablated in differentiated osteoclasts and gain-of-function animals wherein Cdc42Gap, a protein that inactivates the small GTPase, was deleted globally. Cdc42 loss-of-function mice were osteopetrotic and resistant to ovariectomy-induced bone loss, while gain-of-function animals were osteoporotic. Isolated Cdc42-deficient osteoclasts displayed suppressed bone resorption, while osteoclasts with increased Cdc42 activity had enhanced resorptive capacity. We further demonstrated that Cdc42 modulated M-CSF–stimulated cyclin D expression and phosphorylation of Rb and induced caspase 3 and Bim, thus contributing to osteoclast proliferation and apoptosis rates. Furthermore, Cdc42 was required for multiple M-CSF– and RANKL-induced osteoclastogenic signals including activation and expression of the differentiation factors MITF and NFATc1 and was a component of the Par3/Par6/atypical PKC polarization complex in osteoclasts. These data suggest that Cdc42 regulates osteoclast formation and function and may represent a promising therapeutic target for prevention of pathological bone loss.